A Comparison of drought instruments and livelihood capitals: Combining Livelihood and Institutional Analyses to Study Drought Policy Instruments. (26th November 2019) - Hurlbert, Margot A.; Gupta, Joyeeta; Verrest, Hebe
ABSTRACT: Institutional analysis is used to assess macro (in)formal policy approaches while livelihoods analyses takes a micro bottom up approach to analyse how livelihoods can be improved. The two approaches are rarely linked and scarcely applied to the understudied problem of drought. Hence this paper addresses the question: How can the livelihoods approach be combined with institutional analysis and how can such a hybrid method be applied to assess policy instruments aimed at improving, for example, the resilience of agricultural producers to drought? This paper designs a methodology and tests it in three case studies on drought in Alberta (Canada), Coquimbo (Chile), and Mendoza (Argentina). The methodology requires (a) identifying policy instruments (regulatory, market, suasive, and management), and assessing their effectiveness in addressing the (b) local to global drivers of the problem being addressed while (c) improving the resilience of people through contributing to livelihood capitals. The paper concludes first, that different policy mixes are necessary in different geographical areas and circumstances for enhancing livelihood capitals, and second, that it is possible and useful to combine top down institutional analysis with bottom up livelihood capitals.